Post-fire performance of high strength concrete filled stainless steel tubular stub columns - Aryanto, Jason Hutomo (2019)
This project presents an Experimental study of Post-fire Performance of High-strength Concrete Filled Stainless Steel Tubular (HCFSST). Materials utilised for HCFSST in this project included Austenitic Stainless-steel Circular Hollow Section (CHS) stub columns and High Strength Concrete (HSC). The Concentric Compression test was conducted on 16 samples of HCFSST together with 16 material tensile coupon test. The tested parameters in this project involved two dimensions of Circular Hollow Sections: CHS 73x3 and CHS 89x3, two High-strength Concrete grades of C90 and C120, as well as 4 different heating durations of: T0 (No heating, ambient temperature), T15 (15 minutes), T30 (30 minutes), and T45 (45 minutes). The heating process of HCFSST samples followed ISO-834 Standard Fire Curve. Also, two tensile coupons were prepared in compliance with the requirements recommended in EN ISO 6892-1 of each CHS exposed in different heating duration, resulting in a total of 16 tensile coupon tests. Stub Column Tests was conducted at a constant loading rate of 0.3mm/min throughout the testing with 3 Strain Gauge attached at each sample to monitor both transverse and longitudinal strain throughout the test. The load-deformation curves for 16 samples were then obtained. In tensile coupon test, initial loading rate of 0.05mm/min was applied first until the material attained nominal 0.2% Proof Stress, followed with an increased rate of 0.8mm/min loading rate for post-yield stage until the coupons reached its failure. Two Strain Gauge and an extensometer was adopted to monitor coupons strains. Typical material stress-strain curves for coupons were later extracted to be analysed. From post-fire tensile coupon test results, it can be concluded that Young Modulus has generally unchanged while there is a slight reduction in its ultimate stress capacity of the coupons. There is also an increase in the ultimate strain in the sample as the materials become more ductile with increasing heating duration. From stub column tests, it was found that there is a general decrease in its compressive stiffness and the residual ultimate carrying capacity of the HCFSST stub columns. The residual ultimate carrying capacity test result were then assessed in comparison with the predicted resistance of HCFSST stub columns using design codes, namely European Code, American Specification and Australian/New Zealand Standard. These codes are adopted as currently there have been no established post-fire design standards for HCFSST. Hence, corresponding design provisions for CFST at room temperature with modification of its concrete strength was adopted. In general, the assessment showed that the provision by design codes currently led to a safe but undly conservative and scattered prediction of compressive capacity.